2018
DOI: 10.1038/s41598-018-34698-9
|View full text |Cite
|
Sign up to set email alerts
|

Enoxacin and bis-enoxacin stimulate 4T1 murine breast cancer cells to release extracellular vesicles that inhibit osteoclastogenesis

Abstract: Enoxacin and its bone-seeking bisphosphonate derivative, bis-enoxacin, have recently captured attention as potential therapeutic agents for the treatment of cancer and bone disease. No differences in growth or survival of 4T1 murine breast cancer cells were detected at a concentration of 50 µM of enoxacin or bis-enoxacin. Growth was perturbed at higher concentrations. Both 50 µM enoxacin and bis-enoxacin stimulated increases in the number of GW/Processing bodies, but there were minimal changes in microRNA leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…Another possibility is that V‐ATPases are known to be integrated into various metabolic and physiological pathways 46 . BE may disrupt the targeting of V‐ATPases thus leading to the release of extracellular vesicles causing alterations in microRNA levels 47 . Subsequently, stimulation of microRNAs, rescue of p53 48 or stimulation of the JNK pathway may produce a variety of cellular effects that are distinct from BP action on bone.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that V‐ATPases are known to be integrated into various metabolic and physiological pathways 46 . BE may disrupt the targeting of V‐ATPases thus leading to the release of extracellular vesicles causing alterations in microRNA levels 47 . Subsequently, stimulation of microRNAs, rescue of p53 48 or stimulation of the JNK pathway may produce a variety of cellular effects that are distinct from BP action on bone.…”
Section: Discussionmentioning
confidence: 99%
“…All mentioned miRNAs are involved in the regulation of bone remodeling and osteoclastogenesis. Additionally, EVs from enoxacin-treated 4T1 cells enhanced the proliferation of murine macrophage cells [49]. The effective concentration range affecting miRNA biogenesis (see Table 1) was from 50 to 124 µM; however, an achievable serum concentration for a standard clinical dose 400 mg two times a day was ca.…”
Section: Other Consequences Of Enoxacin-mediated Mirna Dysregulationmentioning
confidence: 99%
“…Depleting CD99 in cells affects the amount of CD99 in EVs, and the effect of EVs can be altered by depleting CD99 in Ewing sarcoma cells [ 110 ]. It has been reported that 4T1 cells treated with antibacterial drugs secrete EVs that can inhibit osteoclastogenesis [ 233 ]. A natural killer cell line treated with IL-15-secreted EVs can inhibit cancer growth [ 234 ].…”
Section: Potential Of Evs For Cancer Treatmentmentioning
confidence: 99%